Original paperComplete infarct-related artery revascularization in acute myocardial infarction patients. CORAMI Registry - Siudak, Zbigniew; Mrevlje, Blaz; Januś, Bogdan; Dziewierz, Artur; Rakowski, Tomasz; Legutko, Jacek; Bartuś, Stanisław; Dudek, Dariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction: There are still limited data on the occurrence of multiple stenotic lesions within the infarct-related artery (IRA) in acute myocardial infarction (MI), and there is no consensus on the optimal treatment of this patient subgroup, which varies between centers and operators. Aim: To analyse the clinical efficacy of percutaneous coronary intervention (PCI) strategy of culprit lesion only in patients with myocardial infarction. Material and methods: Patients with acute MI with the presence of at least two significant lesions in the IRA – (1) the target culprit lesion which required immediate stenting (> 50–100% stenosis) and (2) a second distal critical lesion (70–90%) – were included in the registry. Both lesions in the IRA were considered to be independent lesions requiring two separate stent platforms to be covered (no overlap). The decision on the treatment strategy of either complete (CR) or culprit-lesion-only (CLO) revascularization was at the discretion of the operator. Results: There were altogether 95 patients enrolled in the registry, 63 (66%) in the group with CR of the IRA and 32 (34%) with CLO revascularization, which did not differ in terms of baseline demographics. In-hospital and long-term outcomes were similar between the groups. Stent thrombosis at 1 year occurred in 1.6% in CR and in 6.2% in CLO groups respectively (statistically not significant). There were no patients from the CLO group who had a planned percutaneous coronary intervention (PCI) of the 2nd lesion in the IRA during 1-year observation. Conclusions: At 1 year the clinical outcome was similar between those with complete and CLO PCI. Complete coverage of significant lesions did not increase the risk of stent thrombosis or need for repeated revascularization in long-term observation.